Pelatihan Metode Membaca SQ3R untuk Siswa Madrasah Tsanawiah Raudhatusyubban - Istiqamah Istiqamah; Sri Normuliati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This service aims to increase reading interest in tsanawiah madrasah students or equivalent to junior high schools (SMP) with SQ3R reading techniques that can be applied in reading textbooks. The method of activities used in this service in the form of training/workshops and training results are simulated directly to each student through stages (1) Survey (2) Questions/questions (3) Read/read (4) Recite/Recall/Repeat/Retell and (5) Review/review/review. The trainees were 26 students from Tsanawiah Raudhatusyuban Madrasah and involved two teachers. The results of this service show that the reading ability of students of the Tsanawiah madrasah or equivalent to junior high school is still deficient so that the existence of reading training with the SQ3R method is expected to increase students' interest and reading skills.